Pengaruh Kemudahan Pengguna dan Cashback terhadap Minat Beli Ulang Mahasiswa di Marketplace Lazada - Bayu Teta; Selvina Mariana Sitinjak; Jesica Theresia Purba2; Tiurlan Br manullang (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to analyze the effect of ease of use and cashback on students' repurchase intention on the Lazada marketplace. The research employs a quantitative approach with a survey method. The sample was obtained using accidental sampling, involving 55 active student users of Lazada. The instrument used a closed-ended questionnaire with a Likert scale, and both validity and reliability were tested. Data were analyzed using multiple linear regression. The results show that ease of use and cashback both have a significant partial and simultaneous effect on repurchase intention.